Series of 11 photos of dwellings located in the 'Kreis Waldenburg' of the 'Regierungsbezirk Breslau' in the 'Eulengebirge' in Silezia
Series of 11 photos of dwellings located in the 'Kreis Waldenburg' of the 'Regierungsbezirk Breslau' in the 'Eulengebirge' in Silezia.